Carvedilol solid dispersion for enhanced oral bioavailability using rat model - Javier Rueda Arregui, Surya Prakasarao Kovvasu, Priyanka Kunamaneni, Guru V. Betageri (Journal of Applied Pharmaceutical Science, 2019)
The objective of the present study was to develop a solid dispersion formulation to improve oral bioavailability of poorly water-soluble drug carvedilol. Several solid dispersions were prepared by fusion-solvent method mixing different concentrations of Gelucire 44/14 and Gelucire 50/13. To the resultant solid dispersions, microcrystalline cellulose and amorphous fumed silica were added to obtain a free-flowing powder. The dissolution of carvedilol was evaluated using an USP Type-II dissolution apparatus. Solid dispersion with Gelucire 44/14 showed, in general, a lower extent of drug release when compared to Gelucire 50/13 at the same concentrations. Gelucire 50/13 in a ratio of 1 to 1.75 (drug: Gelucire) achieved a drug release of 83% in 4 hours, a 5-fold increase compared to pure carvedilol. When incorporating 10% D-α-tocopheryl polyethylene glycol succinate (vitamin E TPGS/ TPGS) a higher drug release was observed (88%). Parallel artificial membrane permeability assay was used to evaluate the in vitro diffusion. Gelucire- TPGS solid dispersion showed a higher permeability coefficient compared to pure drug. After oral administration to Sprague-Dawley rats, a significant increase in the oral bioavailability of carvedilol was observed when administered as a solid dispersion in combination with Gelucire-TPGS, 169% higher compared to pure drug suspension.
Keywords: Oral bioavailability, solid dispersions, carvedilol, Gelucire, TPGS.